2014
DOI: 10.1016/j.jvs.2014.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiac evaluation before thoracic endovascular aortic repair

Abstract: Background Patients with thoracic aortic disease undergoing thoracic endovascular aortic repair (TEVAR) often have concomitant coronary artery disease and are at risk for perioperative adverse cardiac events. Despite this risk, the need for and extent of preoperative cardiac workup before TEVAR remain undefined. This study seeks to assess the adequacy of a limited cardiac evaluation before TEVAR, including assessment of cardiac symptoms, resting electrocardiography (ECG), and transthoracic echocardiography (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…A recent study reported a low incidence (2.4%) of perioperative adverse cardiac events (e.g., myocardial infarction or cardiac arrest) occurring after TEVAR [6]. That study also found that patients who suffered a cardiac event had an average of 4.2 cardiac risk factors (e.g., hypertension, hyperlipidemia, smoking, diabetes, coronary artery disease, history of myocardial infarction, and peripheral vascular disease) [6]. From among these risk factors, our patient only had hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study reported a low incidence (2.4%) of perioperative adverse cardiac events (e.g., myocardial infarction or cardiac arrest) occurring after TEVAR [6]. That study also found that patients who suffered a cardiac event had an average of 4.2 cardiac risk factors (e.g., hypertension, hyperlipidemia, smoking, diabetes, coronary artery disease, history of myocardial infarction, and peripheral vascular disease) [6]. From among these risk factors, our patient only had hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…This 5.2% incidence of CEs is comparable with published results. 1,2 Of the 150 patients who experienced CEs, 67.3% presented with descending thoracic aortic aneurysm compared with 32.7% with dissection. However, there were no significant differences for incidence of post-TEVAR CEs between aneurysm and dissection patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac events continue to remain a significant cause of morbidity and mortality following TEVAR. 1,2 This makes it necessary to determine risk prediction models that would allow surgeons to identify at-risk patients to provide appropriate perioperative management that would minimize morbidity and improve post-TEVAR outcomes. The present study aims to identify risk factors for post-TEVAR CEs in descending thoracic aortic aneurysm or dissection to allow for optimal management of at-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ganapathi et al 40 examined the role of cardiac testing in TEVAR patients in their retrospective single center review of 463 TEVAR patients. This study found that the incidence of cardiac complications was 2.4%.…”
Section: Intensive Care Unit Management Of Tevarmentioning
confidence: 99%
“…Furthermore, it recommends use of baseline electogardiography and transthoracic echocardiography as sufficient to capture cardiovascular risk. 40 The most recent American College of Cardiology and American Heart Association (ACC/AHA) guidelines for cardiovascular evaluation and management for noncardiac surgery recommend the use of exercise testing only in patients in whom functional capacity cannot be determined. This guideline is only applicable to a select few endovascular abdominal aortic repair (EVAR) and patients presenting for open surgical repair.…”
Section: Intensive Care Unit Management Of Tevarmentioning
confidence: 99%